Theoretical aspects of determination of environmental-and-economic effectiveness of complex utilization of wood - Ferents, Oksana; Kindrat , Rostyslav (Forestry, Forest, Paper and Woodworking Industry, 2013)
Theoretical approaches are determined in relation to the estimation of ecological-economical efficiency of production. Grounded importance of the complex processing of raw material in a wood-working production and determination of him ecological-economical efficiency. The necessity of calculation of indexes of ekologo-ekonomichnoy efficiency of the complex processing of wood is reflected.